PENGARUH PARTISIPASI ANGGARAN PADA SENJANGAN ANGGARAN DENGAN ASIMETRI INFORMASI DAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERASI - Sinta Mahadewi, Anak Agung Sagung (E-Jurnal Akuntansi; Vol 8 No 3 (2014), 2014)
A budget is a financial plan for the future that includes goals and actions that will be taken. The purpose of this study was to determine the effect of budget participation, information asymmetry and organizational commitment on budgetary slack. The research was conducted on the entire Department in the City of Denpasar. The number of samples taken by 77 employees with purposive sampling method. Data collected through questionnaires and research literature. The analysis technique used is Moderated Regression Analysis (MRA). Based on the results of the analysis found that variables budgetary participation has a positive effect on budgetary slack. These results indicate that the higher the level of participation, they will have a tendency to use the advantages of the knowledge that they have to create budgetary slack. Asymmetry of information on the relationship between budgetary participation has a positive effect on budgetary slack. Organizational commitment to the relationship of budget participation on budgetary slack has a negative effect.
Keywords: Partisipasi Anggaran, Asimetri Informasi, Komitmen Organisasi, Senjangan Anggaran